Sarekat Islam dalam Pergerakan Nasional Indonesia di Medan: Kajian Surat Kabar Benih Merdeka, 1919-1942 - Zainul Karim; Yusra Dewi Siregar (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2023)
Sarekat Islam became an important organization in developing the issue of Indonesian nationalism and national movement. This article examines the process of entering and developing Sarekat Islam in Medan and its role as well as its impact on people’s lives. The research was carried out using historical research methods which included gathering sources, source criticism, interpretation, and finally the stage of writing history. The primary sources used are data and information from the contemporary newspaper Benih Merdeka, while the secondary sources are the results of academic research obtained from various scientific journals. This paper concludes that Sarekat Islam entered Medan through several stages, namely personal or individually which then became institutionalized and tended to be dynamic. Then in its development, Sarekat Islam succeeded in mobilizing with more and more people participating in the organization.